Національній академії наук України – 95 - Храмов, Ю.О. (Наука та наукознавство, 2013)
Розкрито передумови створення НАН України, історія її заснування, коротка історія становлення фундаментальної академічної науки та її розвиток, стан академічної науки в незалежній Україні. This paper reveals the prerequisites of the National Academy of Sciences of Ukraine, the story of its founding, a brief history of the formation of basic academic science and its development, the state of academic research in an independent Ukraine.